Firm behavior during an epidemic - Luiz Brotherhood; Vahagn Jerbashian (Global Labor Organization (GLO), 2020)
We derive a model in which firms operate in an epidemic environment and internalize infections among their employees in the workplace. The model is calibrated to fit the properties of the Covid-19 epidemic. We show that firms have incentives to fight against infections and can do so very effectively by increasing teleworking and rotating employees between on-site work, teleworking, and leave. Subsidies to sick leave reduce the cost of sick workers and raise workplace infections. Furlough policies are successful in reducing infections and saving lives. Firms delay and weaken the fight against infections during economic downturns.
Keywords: C63; D20; D21; I10; I18; L23; 330; Covid-19; epidemic; firm behavior; on-site work; policies; teleworking